Patterns in Stable Isotope Values of Nitrogen and Carbon in Particulate Matter from the Northwest Atlantic Continental Shelf, from the Gulf of Maine to Cape Hatteras - Oczkowski, Autumn; Kreakie, Betty; McKinney, Richard A.; Prezioso, Jerry (Frontiers in Marine Science, 2016)
Stable isotope measurements of nitrogen and carbon (δ15N, δ13C) are often used to characterize estuarine, nearshore, and open ocean ecosystems. Reliable information about the spatial distribution of base-level stable isotope values, often represented by primary producers, is critical to interpreting values in these ecosystems. While base-level isotope data are generally readily available for estuaries, nearshore coastal waters, and the open ocean, the continental shelf is less studied. To address this, and as a first step towards developing a surrogate for base-level isotopic signature in this region, we collected surface and deep water samples from the United States’ eastern continental shelf in the Western Atlantic Ocean, from the Gulf of Maine to Cape Hatteras, periodically between 2000 and 2013. During the study, particulate matter δ15N values ranged from 0.8 to 17.4 ‰, and δ13C values from -26.4 to -15.6 ‰ over the region. We used spatial autocorrelation analysis and random forest modeling to examine the spatial trends and potential environmental drivers of the stable isotope values. We observed general trends towards lower values for both nitrogen and carbon isotopes at the seaward edge of the shelf. Conversely, higher δ15N and δ13C values were observed on the landward edge of the shelf, in particular in the southern portion of the sampling area. Across all sites, the magnitude of the difference between the δ15N of subsurface and surface particulate matter (PM) significantly increased with water depth (r2 = 0.41, df = 35, p < 0.001), while δ13C values did not change. There were significant positive correlation between δ15N and δ13C values for surface PM in each of the three marine ecoregions that make up the study area. Stable isotope dynamics on the shelf can inform both nearshore and open ocean research efforts, reflecting regional productivity patterns and, even possibly, large-scale climate fluctuations.